Ushering URM STEM teachers into STEM spaces: A model to increase STEM community access and belonging - King Miller, Beverly; Burnett, Camille S. (American Journal of STEM Education, 2025)
Historically Black Colleges and Universities (HBCUs) are poised to address underrepresentation and promote diversity in STEM fields by providing K-12 students with teachers from diverse backgrounds. This conceptual paper examines science, technology, engineering, and mathematics (STEM) initiatives aimed at supporting the inclusion of underrepresented and racially minoritized (URM) students, who will become future STEM teachers. Through new initiatives informed by best practices, researchers have proposed three strategies to integrate URM students into STEM communities and foster a sense of belonging among them as future STEM teachers. Preliminary findings from pilot studies support the notion that these strategies can be used to mitigate imposter syndrome among URM STEM students, thereby increasing their sense of belonging and inclusion within various STEM communities.